2016
DOI: 10.1002/ajcp.12063
|View full text |Cite
|
Sign up to set email alerts
|

Social Network Characteristics, Social Support, and Cigarette Smoking among Asian/Pacific Islander Young Adults

Abstract: Cigarette smoking may be one of the factors contributing to the high levels of cancer-related mortality experienced by certain Asian/Pacific Islander (A/PI) subgroups (e.g., Native Hawaiian). Given the collectivist cultural orientation attributed to A/PI groups, social strategies are recommended for substance abuse or smoking cessation treatment among A/PI. However, research examining how social network characteristics and social support relate to smoking across A/PI subgroups has been lacking. This study inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
2
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 61 publications
0
20
2
3
Order By: Relevance
“…Though the prevalence is consistently low, the grouping of Asians and Pacific Islanders together because of sample sizes may mask areas of concern among the subgroups. In Hawaii, for instance, Native Hawaiians have the highest prevalence of smoking [20]. Thus, despite pregnancyspecific smoking rates among the Native Hawaiian subgroup, smoking during pregnancy might be a concern among this population.…”
Section: Discussionmentioning
confidence: 99%
“…Though the prevalence is consistently low, the grouping of Asians and Pacific Islanders together because of sample sizes may mask areas of concern among the subgroups. In Hawaii, for instance, Native Hawaiians have the highest prevalence of smoking [20]. Thus, despite pregnancyspecific smoking rates among the Native Hawaiian subgroup, smoking during pregnancy might be a concern among this population.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the same paper, the authors pointed out that social support and social cohesion may be associated with higher smoking rate in groups with high rates of smoking, which is in line with previous research [25][26][27] and the current study. Past research has shown that the greater the social network size, the more likely a person is to smoke, especially in Asian cultures where collectivism is valued [28]. China consumes about 40% of the world's cigarettes, and the prevalence of smoking remained high in men (54.0% prevalence for current-smoking) [29].…”
Section: Tobacco Alcohol Use and Dietmentioning
confidence: 99%
“…Young adults (18–25 years old) have the highest smoking prevalence compared with other age groups, according to a 2014 report by the Substance Abuse and Mental Health Services Administration ( Substance Abuse and Mental Health Services Administration, 2014 ). Minority, young adults are particularly at risk for smoking due to several key factors: past cultural-based traumas, social and family norms, discrimination, persistent economic hardships, and low college-degree attainment ( Kassel, Stroud, & Paronis, 2003 ; Pokhrel et al, 2016 ; U.S. National Cancer Institute, 2017 ; Walker & Loprinzi, 2014 ). Nationally, Samoans and Tongans are more likely than Native Hawaiians to live in poverty (16%, 19% vs. 12%) ( American Community Service Office, 2012 ) and less likely to earn a bachelor's degree (12%, 13% vs. 18%) ( American Community Service Office, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Nationally, Samoans and Tongans are more likely than Native Hawaiians to live in poverty (16%, 19% vs. 12%) ( American Community Service Office, 2012 ) and less likely to earn a bachelor's degree (12%, 13% vs. 18%) ( American Community Service Office, 2012 ). Young adult Samoans and Tongans may be especially prone to smoking onset and progression because of strongly embedded social norms around tobacco use ( Pokhrel et al, 2016 ), which extend to their country of origin. A 2015 report of tobacco use in the Pacific region revealed that adults in Samoa and Tonga had high rates of current smoking at 38.8% and 30.3%, respectively, in part due to weak tobacco control policies ( Kessaram, McKenzie, Girin, et al, 2015 ; Tautolo, Schluter, Paterson, & McRobbie, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation